Eksplorasi Pengembangan Dimensi Konseptual Pembelajaran Al-Qur’an Hadis untuk Meningkatkan Literasi Keagamaan Kelas VII di SMPN 5 Tuban - Fatimatuz Zahro’; Umu Fahiimah (CV. ITTC INDONESIA, 2025)
This study aims to explore the needs, design development, and implementation of conceptual dimensions in teaching the Qur'an and Hadith as a strategy to improve religious literacy for seventh-grade students at SMPN 5 Tuban. Using a descriptive and exploratory qualitative approach, data were obtained through observation, interviews with teachers and students, and document analysis. Findings from this study indicate that the current learning process is still focused on technical aspects, such as tajwid and reading skills, while understanding meaning, interpreting values, contextualizing teachings, and reflecting on activities have not been fully integrated. Additional findings indicate that students find it easier to understand lessons when teachers relate them to direct experiences, while teachers need systematic guidance to design more conceptual and applicable learning steps. Based on the findings, this study produced a concept map for developing dimensions in the Qur'an and Hadith, which includes understanding verses, moral values, contextualization, reflection, and supporting strategies such as reflective approaches, experience discussions, case studies, and the use of visual media. This model has the potential to strengthen religious literacy in a more comprehensive manner and in accordance with the developmental needs of students. This study suggests that further trials be conducted in diverse school contexts to obtain a more complete picture of the effectiveness of the developed model.